Improvement of standard-legal and methodical ensuring performance of the federal budget - F. A. Shogenova (Путеводитель предпринимателя, 2020)
Article is devoted to the necessity of further improvement of standard and legal regulation at all stages of the budgetary process and creation of the effective mechanism of management efficiency of the budgetary expenses.